Intregrated Marketing Plan of Beauty and Health Center (Case: Voila) - Dewi, Riani Saraswati; Larso, Dwi (The Indonesian Journal of Business Administration, 2014)
Abstract. Growing trend of beauty trends has made the rise of beauty salons in Bandung. The need of pampering and increase good freshness from hectic activities made the idea of making service facility where consumers can enjoy all in one package. With the combination facilities consisting of a salon and fitness classes, Voila became one-stop beauty and health center. Business issues faced by Voila today are stagnancy growth revenue where revenues do not achieve sales target in the initial business plan. Problem solving was restricted into two goals categories that are increase brand awareness and gaining sales revenue. Root cause was analyzed from Voila internal data and customer perception via questionnaire. The analysis obtained that Voila have no marketing action and the business have no uniqueness with compared to other competitors. To solved the problem, Voila need to do marketing strategies and product modification strategy. Implementation plan was divided into immediate and long-term program. For immediate program, Voila strategies were increasing brand awareness by viral marketing, improved productivity by adding temporary high skilled employee and trained low skilled employee also maintain company flow by created financial structure. Marketing strategy can be done by improving website, update in social media, also active in events related to beauty and health issue. Moreover, productivity in health studio will be improved by adding new variation of fitness class. The synergy between salon and fitness studio can be built by making integrated system for each product. For long-term program, Voila planned for product modification strategy by creating new service in medical-based beauty treatment and create additional facility such as café. In addition medical-base beauty service, Voila will collaborate with dermatologist to create skin care salon medical based, also making mass product of hair and skin treatment. Keywords: marketing, service, brand awareness, beauty and health